1990
DOI: 10.1007/bf01344301
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic neoplasia inMya arenaria: Prevalence and indices of physiological condition

Abstract: A field survey of hematopoietic neoplasia (Hn) in the soft shell clam Mya arenaria (L.) was undertaken using an immunoperoxidase diagnostic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…Determining the temperature range of the RT activity using the PERT assay could lead to a better understanding of the seasonal nature of the disease that has been reported by several authors (Cooper et al 1982, Appeldoorn et aI. 1984, Farley et al 1986, Brousseau 1987, Leavitt et al 1990). addition all.^, testing mussels and cockles with DN for RT activity using the methods described here would determine if the same patterns of enzyme activity existed, and potentially, if similar mechanisms are responsible for this condition in different species of bivalves.…”
Section: Discussionmentioning
confidence: 95%
“…Determining the temperature range of the RT activity using the PERT assay could lead to a better understanding of the seasonal nature of the disease that has been reported by several authors (Cooper et al 1982, Appeldoorn et aI. 1984, Farley et al 1986, Brousseau 1987, Leavitt et al 1990). addition all.^, testing mussels and cockles with DN for RT activity using the methods described here would determine if the same patterns of enzyme activity existed, and potentially, if similar mechanisms are responsible for this condition in different species of bivalves.…”
Section: Discussionmentioning
confidence: 95%
“…Decreases in feeding rates could be attributed to non-specific narcosis associated with the accumulation of low molecular weight hydrocarbons (Donkin et al 1990), whereas the increases in energy expenditures through increased metabolic rates could be related to the accumulation of TBT through effects on oxidative phosphorylation (Widdows et al 1990). Bivalves collected along the same gradient showed changes in biochemical composition, especially in the ratio of neutral to polar lipids and carbohydrate content (Leavitt et al 1990a).…”
Section: Discussionmentioning
confidence: 99%
“…Both Reinisch et al (1984) and Leavitt et al (1990b) reported a high prevalence of hematopoietic neoplasia in M. arenaria populations from a site in New Bedford Harbor in comparison with uncontaminated sites in Buzzards Bay. Leavitt et al (1990b) observed an overall prevalence of 39.3%. Unlike populations of Mytilus, there were no differences in gonadal development, condition indices, or lipid content between clam populations from New Bedford Harbor and a reference site (Little Buttermilk Bay, Massachusetts), except with the most advanced stage of hematopoietic neoplasia.…”
mentioning
confidence: 96%
See 2 more Smart Citations